1996
DOI: 10.1039/cc9960002105
|View full text |Cite
|
Sign up to set email alerts
|

Making radical cations live longer

Abstract: hexafluoropropan-2-o1 (HFP) appears as a solvent with properties at the extreme. Its combination of low nucleophilicity, high hydrogen bonding donor strength, low hydrogen bonding acceptor strength, high polarity and high ionizing power makes it an ideal solvent for radical cations. Applications of HFP as a solvent for EPR spectroscopy and mechanistic studies of radical cations as intermediates in electrophilic aromatic substitution, photochemistry and spin trapping are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
137
0
2

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(144 citation statements)
references
References 42 publications
4
137
0
2
Order By: Relevance
“…We therefore conclude that the chlorination reaction occurs after the complete iododesilylation reaction of 3 that is generally very fast. [12] Using ESR and UV spectroscopy, Eberson et al demonstrated the ability of iodine monochloride to act as oxidizing reagent of aromatic compounds, [13] however to the best of our knowledge its role as tandem iodination-chlorination reagent has not been reported so far. We propose a mechanism wherein compound 4 is oxidized by the excess of iodine monochloride to give the radical cation C (Scheme 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We therefore conclude that the chlorination reaction occurs after the complete iododesilylation reaction of 3 that is generally very fast. [12] Using ESR and UV spectroscopy, Eberson et al demonstrated the ability of iodine monochloride to act as oxidizing reagent of aromatic compounds, [13] however to the best of our knowledge its role as tandem iodination-chlorination reagent has not been reported so far. We propose a mechanism wherein compound 4 is oxidized by the excess of iodine monochloride to give the radical cation C (Scheme 3).…”
Section: Resultsmentioning
confidence: 99%
“…1 Hand 13 C NMR spectra were recorded using either Bruker (AC 500/ AVIII 700) or JEOL (ECX 400/Eclipse 500) instruments. Chemical shifts (in δ units, ppm) are referenced to TMS by using CHCl 3 (δ = 7.26 ppm) and CDCl 3 (δ = 77.0 ppm) as the internal standards for 1 H-and 13 C NMR spectra, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…This seems to be due to the extremely low nucleophilicity of HFIP. 14 In contrast, HFIP acted as a nucleophile in the presence of Si-piperidine to afford 2a in good yield (entry 2). The HFIP/MeCN co-solvent system (entries 35) and silica gel supported bases (entries 57) were optimized, and then entry 5 was selected as the best reaction conditions.…”
Section: Resultsmentioning
confidence: 99%
“…First, 15 N-CIDNP results obtained during the photonitration of 1 with 15 N-labelled tetranitromethane will be presented. The appearance of free radicals during the photoreaction of tetranitromethane with activated arenes has already been shown using time-resolved spectroscopy and ESR [7] [12] , and has been postulated to occur during the photoreaction with 1 [13] The second reaction is the nitration of 1 with dilute nitric acid, which will be studied by 15 N-CIDNP in water and different organic solvents under the conditions customary in synthetic work. The radical character of the reaction (NAC, Eqs.…”
mentioning
confidence: 96%